New mobilities in Europe : Polish migration to Ireland post-2004. - Krings, Torben (Manchester University Press, 2016)
This book examines Polish migration to Ireland in the context of 'new mobilities in Europe'. It includes detailed accounts of the working lives of a group of mainly skilled Polish migrants in Dublin, and traces their careers and aspirations as Ireland moved from 'boom to bust'.